Annotation of additional evolutionary conserved microRNAs in CHO cells from updated genomic data. Issue 7 (8th April 2015) - Diendorfer, Andreas B.; Hackl, Matthias; Klanert, Gerald; Jadhav, Vaibhav; Reithofer, Manuel; Stiefel, Fabian; Hesse, Friedemann; Grillari, Johannes; Borth, Nicole
ABSTRACT MicroRNAs are small non‐coding RNAs that play a critical role in post‐transcriptional control of gene expression. Recent publications of genomic sequencing data from the Chinese Hamster (CGR) and Chinese hamster ovary (CHO) cells provide new tools for the discovery of novel miRNAs in this important production system. Version 20 of the miRNA registry miRBase contains 307 mature miRNAs and 200 precursor sequences for CGR/CHO. We searched for evolutionary conserved miRNAs from miRBase v20 in recently published genomic data, derived from Chinese hamster and CHO cells, to further extend the list of known miRNAs. With our approach we could identify several hundred miRNA sequences in the genome. For several of these, the expression in CHO cells could be verified from multiple next‐generation sequencing experiments. In addition, several hundred unexpressed miRNAs are awaiting further confirmation by testing for their transcription in different Chinese hamster tissues. Biotechnol. Bioeng. 2015;112: 1488–1493. © 2015 The Authors. Biotechnology and Bioengineering Published by Wiley Periodicals, Inc.